Triad Connections to Pedagogical Competence in Teacher Education - Bello, M. I; Egunsola, A. O. E. (Kashere Journal of Education, 2021)
Teacher Education revolves round instilling skills and abilities to help teachers acquire knowledge of transferring knowledge to learners with ease, referred to as pedagogical competence, hence training institutes were established in realization of this stride. Notably, skills and abilities in instructional design, classroom management, and classroom assessment techniques among others are instilled while undergoing professional training. These attributes when instilled help teachers to design a systematic process of translating a plan of action into set of activities, materials and procedures. But achieving the systematic process alone, which is the instructional design cannot on its own bring about learning, without a robust relationship between students and teachers, which ultimately requires skills and abilities to perform superbly in classroom management techniques as well. But of note, skills and abilities in instructional design and classroom management only, cannot guarantee achievement recorded in lesson delivery, without classroom assessment techniques. Apart from instilling these attributes, a trainee (pre-service teacher) is also expected to proceed for teaching practice upon reaching certain level and academic threshold. During this period, triad directly involved through collaboration includes pre-service teachers, university supervisors and cooperative supervisors. This collaboration gives direction, guidance, supervision and mentoring by supervisors on to the pre-service teachers. Subsequently outcome from this collaboration entails either to consolidate on the strengths observed or make amends to weaknesses observed during the exercise, which ultimately has direct effect on the teacher education as a whole.